Somatostatin receptor PET/MR imaging of large vessel inflammation in active compared with inactive vasculitis and atherosclerosis. (3rd October 2022) - Tarkin, J; Corovic, A; Wall, C; Nus, M; Gopalan, D; Huang, Y; Imaz, M; Zulcinski, M; Reynolds, G; Morgan, A W; Jorgensen, H F; Mallat, Z; et al.
Abstract: Background: Use of 18F-FDG PET in large vessel vasculitis (LVV) is limited by non-specific uptake due to arterial remodelling and/or atherosclerosis leading to diagnostic uncertainty. Purpose: To investigate somatostatin receptor 2 (SST2) as a novel inflammation-specific PET imaging target in LVV. Methods: In a prospective observational cohort study, we tested the ability of PET/MRI using two somatostatin receptor tracers (68Ga-DOTATATE and 18F-FET-βAG-TOCA) to differentiate active from inactive LVV, and aortic atherosclerosis in patients with recent myocardial infarction. Ex vivo mapping of the imaging target was performed using immunofluorescence microscopy, imaging mass cytometry, and bulk, single-cell and single-nuclei RNA sequencing of temporal artery biopsies from LVV patients. Results: Sixty-one participants were included (LVV, n=27; myocardial infarction ≤2 weeks, n=25; control subjects with an oncological indication for imaging, n=9). LVV patients (mean age 58 [SD 16] years; 78% female; 63% active or grumbling disease) had giant cell arteritis (n=13), Takayasu arteritis (n=13), or unspecified LVV (n=1). Baseline index vessel SST2 PET maximum tissue-to-blood ratio (TBRmax) was 61.8% (95% CI 31.5–99.0%, p<0.0001) higher in patients with active/grumbling LVV than inactive LVV, and 34.6% (95% CI 15.1–57.6%, p=0.0002) higher than recent myocardial infarction (Fig. 1a–c; arrow: PET signal; arrowhead: aortic thickening; asterisk: aortic atherosclerosis), with good diagnostic accuracy (AUC ≥0.86, p<0.001 for both). None of the control subjects without LVV or MI had increased arterial SST2 PET signal (Fig. 1d). Mean aortic TBRmax was strongly correlated with Indian Takayasu Clinical Activity Score (r=0.82 [95% CI 0.46–0.95], p=0.001) and maximum wall thickness on MRI (r=0.68 [95% CI 0.31–0.87], p=0.002). SST2 PET/MRI was generally consistent with 18F-FDG PET/CT in LVV patients with contemporaneous scans (Fig. 1a, b), but with very low background signal in the brain and heart allowing for unimpeded assessment of nearby coronary, myocardial, and intracranial artery involvement. On follow-up imaging after a mean 9.3 (SD 3.2) months, clinically effective treatment for LVV was associated with a 0.49 ±SEM 0.24 (p=0.04; 22.3%) reduction in SST2 PET TBRmax, with good scan-scan repeatability in inactive LVV patients with no change in treatment (ICC 0.86, 95% CI 0.04–0.99). SST2 localised to macrophages, pericytes, and perivascular adipocytes in inflamed arterial specimens (Fig. 2; a: H&E; b: imaging mass cytometry; arrow: SST2/CD68 co-staining). SSTR2-expressing macrophages co-expressed pro-inflammatory markers (S100A8, S100A9). Specific SST2 radioligand binding was confirmed by autoradiography in LVV specimens. Conclusion: This is the first study to examine SST2 PET/MRI in LVV and to provide histological and gene expression data for validation. Here we show this novel approach holds major promise for diagnosis and therapeutic monitoring in LVV. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Wellcome Trust; Imperial NIHR Biomedical Research Centre